Early clinical experience using telemedicine for the management of patients with varicose vein disease. (January 2019) - Kavousi, Yasaman; Al-Adas, Ziad; Crutchfield, Janelle M; Karamanos, Efstathios; Swanson, Christine; Lin, Judith C
Introduction: The use of telemedicine services may be effective in the perioperative management of patients with varicose veins. Methods: Over a seven-month period, patients with varicose veins were evaluated in the virtual clinic via two-way secure videoconferencing or the traditional clinic by the same physician provider. Data sources included institutional Vascular Quality Initiative registry and patient satisfaction surveys. Results: Among a total of 121 patients with varicose veins who underwent endovenous catheter ablation of the saphenous vein, 20 patients (16.5%) chose the telemedicine clinic (Group A) and 101 patients (83.5%) chose the traditional clinic (Group B) for their perioperative management. Comparing Group A and Group B, the mean age was 59.2 ± 12.1 versus 59.6 ± 13.0, respectively ( p = 0.944); women were 75% versus 73.3%, respectively ( p = 0.872); African Americans comprised 5% versus 22.8%, while Caucasians comprised 95% versus 63%, respectively ( p = 0.049). Half of the telemedicine patients had multiple virtual visits for a total of 31 virtual encounters. Among telemedicine patients using SurveyMonkey®, 29 telemedicine encounters (93.5%) reported that their virtual visit is "Yes, definitely" or "Yes, somewhat" more convenient over traditional methods. All patients answered that they were able to communicate clearly with the provider, able to have their questions answered, and able to clearly hear and see the provider via telemedicine methods. Discussion: Telemedicine services enable another means to deliver high-quality care for patients with venous disease in a safe and coordinated manner. Patients with varicose veins are highly satisfied with the use of telehealth services over the traditional healthcare delivery model.